PERIODIC PARALYSIS - Onegin, Е. V.; Mantsevich, O. V. (Zhurnal Grodnenskogo gosudarstvennogo medit͡s︡inskogo universiteta, 2021)
Periodic paralysis (paroxysmal myoplegia) is a rare neuromuscular disorder caused by mutations in the sodium, calcium, and potassium channel genes of skeletal muscle. Common features of primary periodic paralysis are autosomal dominant inheritance, changes in serum potassium levels as a result of a defect in ion channels, and the onset of the disease in the first or second decade of life. Clinically, PP is manifested by episodic attacks of muscle weakness that occur at irregular intervals, attacks are often associated with food or rest after exercise, sometimes accompanied by myotonia. Periodic paralysis is rare in the general population and, as a result, prospective clinical trials of treatment interventions are limited. Due to the low prevalence of primary PCBs and limited treatment options, few prospective studies are available to develop treatment recommendations based on anecdotal evidence and patient case reports. Treatment options include provocation prevention, potassium and carbonic anhydrase inhibitors.